Effects of soy protein isolate hydrolysate on physicochemical properties and in vitro digestibility of corn starch with various amylose contents. (1st November 2022) - Zhu, Zhijie; Wang, Caihong; Mei, Liping; Xue, Wenwen; Sun, Chengyi; Wang, Yiqun; Du, Xianfeng
Abstract: To explore the interaction regarding protein and corn starch with various amylose contents, high amylose corn starch (HACS), normal corn starch (NCS), and waxy corn starch (WCS) were co-heated with soy protein isolate hydrolysate (SPIH), and the physicochemical properties and in vitro digestibility of each of the three combined materials was analyzed. The SPIH inhibited the in vitro digestion of HACS and NCS, but promoted the in vitro digestion of WCS. SPIH restricted the hydration and expansion of NCS and WCS and increased their gelatinization temperatures; however, SPIH had no significant effect on HACS. It was found that the microstructure of the three types of corn starch were significantly different after freeze-drying because of the different distribution of water molecules in the samples with various amylose contents during gel formation. The setback (SB) and peak viscosity (PV) values of these three types of corn starch reduced with the increase of SPIH mainly because SPIH inhibits the interaction of starch chains. This research lead to a novel idea of using corn starch with various amylose contents in food. Highlights: SPIH has different impacts on water digestibility of the three kinds of corn starch. The addition of SPIH improved the water mobility of the HACS-SPIH complexes gel. SPIH delayed gelatinization of WCS and NCS, but it had no significant effect on HACS. The addition of SPIH reduced the setback value of three kinds of corn starch.